FUTURE OF DIGITAL MARKETING IN INDIA – OPPORTUNITIES AND CHALLENGES - Babita, R.; Rekha, N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The emergence of digital marketing has become an essential part of marketing for businesses today, leading to a gradual replacement of traditional marketing methods. Maintaining constant communication with customers before, during, and after purchase has become vital, and digital marketing enables marketers to better understand customer tastes, preferences, and choices through the use of messages, notifications, emails, and reminders. Digital marketing has become an essential part of the marketing mix for businesses in India as it offers a cost-effective and efficient way to reach out to potential customers, build brand awareness, and drive sales. With the continuous advancement of technology and the increasing usage of digital platforms, digital marketing is expected to become even more critical for businesses in the future. This paper aims to provide insight into the current state of digital marketing in India, highlighting the opportunities and challenges that businesses face as they shift their focus to digital platforms.